Alterações sexo-específicas na memória e homeostase glutamatérgica induzidas por bisfenol A em camundongos: efeito do disseleneto de difenila - Jardim, Natália da Silva (2017)
Bisphenol A (BFA) is an endocrine disruptor with high toxicological potential, used in the manufacture of synthetic polymers, including food and beverage packaging. Even though the deleterious effects of BPA exposure have been well reported, mainly in the early stages of life, none possible therapeutic intervention was developed. In this sense, diphenyl diselenide, (PhSe)2, one of the most studied organic selenium compounds, is a pleiotropic molecule with great therapeutic potential at pharmacological doses. The scientific literature shows different pharmacological properties; among them, the protective effects on the cognitive impairment induced in different experimental models were already described. Taking it into account, the objective of the present dissertation was to investigate the effects of (PhSe)2 on the memory impairments induced by BPA exposure to male and female mice and the possible involvement of glutamatergic system in these effects. Three-week-old male and female Swiss mice received BPA (5 mg/kg), intragastrically, from 21st to 60th postnatal day. After, the animals were intragastrically treated with (PhSe)2 (1 mg/kg) during seven days. The mice performed the behavioral memory tests, Morris water maze, object recognition and step-down passive avoidance. The [3H] glutamate uptake and NMDA receptor subunits (2A and 2B) analyses were carried out in the hippocampus and cerebral cortex of mice. The results demonstrated that the BPA exposure induced impairment of object recognition memory in both sexes. However, it caused impairments in spatial memory in female and in the passive avoidance memory in male mice. Besides, BPA caused a decrease in the [3H] glutamate uptake and NMDA receptor subunits in the cortical and hippocampal regions depending on the sex. The effects of treatment with (PhSe)2 on reversing the alterations in the different types of memory caused by exposure to BFA were independent of sex. As well as the restorative effects of this compound in the [3H] glutamate uptake and NMDA receptor subunits levels in the hippocampus and cortex of mice. In conclusion, the results of this study showed that subchronic exposure to BFA during the brain development period induced damage in the memory formation in a sex-dependent manner and these effects may be related to alterations in the glutamatergic homeostasis. However, (PhSe)2 reversed all behavioral and molecular changes in a sex-independent manner, demonstrating to be a potential candidate for the treatment of memory damage caused by exposure to BPA in mice.